2018
DOI: 10.1016/j.ymthe.2018.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Biochemical Abnormalities and Improved Muscle Function in a Phase I/II Clinical Trial of Clenbuterol in Pompe Disease

Abstract: This 52-week, phase I/II double-blind, randomized, placebo-controlled study investigated the novel use of clenbuterol in late-onset Pompe disease (LOPD) stably treated with ERT. Eleven of thirteen participants completed the study. No serious adverse events were related to clenbuterol, and transient minor adverse events included mild elevations of creatine kinase, muscle spasms, and tremors. At week 52, the 6-min walk test distance increased by a mean of 16 m (p = 0.08), or a mean of 3% of predicted performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 47 publications
(83 reference statements)
1
26
0
1
Order By: Relevance
“…In humans, skeletal muscle hypertrophy has been reported after chronic treatment with other beta 2 ‐agonists, but only a few studies have investigated the effect of chronic clenbuterol treatment. Maltin et al reported increases in muscle strength after 4 weeks of postoperative recovery with clenbuterol treatment (40 μg/day) compared with a placebo group, and Koeberl et al reported increases in functional tests after 52 weeks of clenbuterol treatment (up to 160 μg/day) in patients with Pompe disease. While neither of these two studies demonstrated clenbuterol‐induced skeletal muscle hypertrophy, the increases in muscle performance indicate muscular adaptation to clenbuterol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, skeletal muscle hypertrophy has been reported after chronic treatment with other beta 2 ‐agonists, but only a few studies have investigated the effect of chronic clenbuterol treatment. Maltin et al reported increases in muscle strength after 4 weeks of postoperative recovery with clenbuterol treatment (40 μg/day) compared with a placebo group, and Koeberl et al reported increases in functional tests after 52 weeks of clenbuterol treatment (up to 160 μg/day) in patients with Pompe disease. While neither of these two studies demonstrated clenbuterol‐induced skeletal muscle hypertrophy, the increases in muscle performance indicate muscular adaptation to clenbuterol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The most sensitive measure for biochemical correction of muscle in Pompe disease is glycogen content 16 . Glycogen content was quantified by a sensitive biochemical assay that has advantages over glycogen staining 17 . Adult GAA-KO mice that were injected with 3E+10 vg had decreased glycogen content in the heart in comparison with mice injected with PBS or with 3E+9 vg (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…The adjunctive therapy with b2 agonists is under development in Pompe disease. 32,33 Salmeterol represents another option for this strategy that could be especially beneficial in the context of liver depot gene therapy. Importantly, an inhaled formulation of salmeterol has been approved for clinical use, and oral administration might be easily developed for the treatment of Pompe disease.…”
Section: Discussionmentioning
confidence: 99%
“…34 A recent clinical trial revealed safety and efficacy for clenbuterol treatment in patients who were stably treated with ERT, suggesting that b2 agonists might be effective as adjunctive therapy in Pompe disease. 32 Salmeterol was chosen for evaluation with liver depot gene therapy in GAA-KO mice, based upon prior evidence that b2 agonists were beneficial during GAA replacement in Pompe disease. [8][9][10]33,35 Previously, salmeterol was evaluated with an AAV vector that expressed GAA ubiquitously with a chicken b-actin promoter and cytomegalovirus enhancer, and only the cardiac response was improved by salmeterol administration.…”
Section: Discussionmentioning
confidence: 99%